The Influence of Self-Efficacy and Family Support through Student Involvement in Teaching Practice on Teacherpreneurship - Hidayatussholihah, Ulya (Jurnal Profesi Keguruan, 2025)
This study aimed to build structural modeling of teacherpreneurship spirit determinants in prospective teacher students and analyze the influence of self-efficacy and family support on the teacherpreneurship spirit of economic education students through student involvement in Lantip. This study uses the IEO Astin Model theory proposed by A.W. Astin (1984). This study used a quantitative approach with a causality design based on structural modeling and testing of variable relationships. The research methods used are descriptive statistical analysis and Partial Least Square-Structural Equation Modeling analysis. The results of this study indicate that self-efficacy and family support have a positive and significant effect on student involvement in teaching practice. Self-efficacy, family support, and student involvement in teaching practice positively and significantly affect teacherpreneurship. Self-efficacy has a positive and significant effect on the spirit of teacherpreneurship through student involvement in teaching practice, and family support has a positive and insignificant effect on the spirit of teacherpreneurship through student involvement in teaching instruction. The suggestion is for pre-teacher students to be more active in increasing their insight to improve the spirit of teacherpreneurship and become professional teachers.